2 x 2 − 1 + 2 x 2 + 1 2
For real x , find the minimum value of the expression above.
Give your answer to 2 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
As always you carry on writing your one line solutions... ;-) + 1 ...
How is f(t) increasing for t>0 or t=0 ? What is the rule?
Log in to reply
f ( t ) is undefined for t = 0 and decreasing for 0 < t ≤ 2 . We care for the case t ≥ 2 only, since t = 2 x 2 + 1 ≥ 2 . In that case f ( t ) is increasing since f ′ ( t ) is positive.
f ( x ) = 2 x 2 − 1 + 2 x 2 + 1 2 f ′ ( x ) = 2 x ( 2 x 2 ) ( ln 2 ) − ( 2 x 2 + 1 ) 2 2 ( 2 x ( 2 x 2 ) ( ln 2 ) ) = 2 x ( ( 2 x 2 ) ( ln 2 ) ( ( 2 x 2 + 1 ) 2 ( 2 x 2 + 1 ) 2 − 2 ) ) We can see term written in blue is always positive therefore sign of f ′ ( x ) is governed by the sign as x . ⟹ f ′ ( x ) > 0 ∀ x > 0 ⟹ f(x) is increasing in ( 0 , ∞ ) and f ′ ( x ) < 0 ∀ x < 0 ⟹ f(x) is decreasing in ( − ∞ , 0 ) And therefore has a global minima at x = 0 . f ( 0 ) = 1 Which is the required minimum value of f ( x )
N O T E : − ( 1 ) . x 2 > 0 ⟹ 2 x 2 > 1 ⟹ 2 x 2 + 1 > 2 . And hence blue term is always positive.
Here's a way I first approached the problem and got it wrong.. :-) ( 2 ) . ( 2 x 2 + 1 + 2 x 2 + 1 2 ) − 2 Apply A M − G M on coloured terms to get minimum value as 2 ( 2 − 1 ) but that's wrong since case for equality gives: 2 x 2 + 1 = 2 While we previously noted that 2 x 2 + 1 > 2 so A M − G M could not be applied this way and hence gives wrong result..
P.S:- Graphing calculator was also a option but I wanted to write a solution involving pure calculus..
Check f ( 0 ) = 1 not 2
Log in to reply
Typo ... BTW Nice question ... I got it right in the second attempt ;-)
f ′ ( x ) < 0 for all x<0: small typo there
Problem Loading...
Note Loading...
Set Loading...
Make a substitution t = 2 x 2 + 1 with t ≥ 2 since x 2 ≥ 0 . Now f ( t ) = t − 2 + t 2 is increasing for t ≥ 2 since f ′ ( t ) = 1 − t 2 2 ≥ 2 1 , so that the minimum of f ( t ) on the interval [ 2 , ∞ ) is f ( 2 ) = 1